The Relationship between Basic Sanitation Quality and Food Safety for Food Preparation in Restaurants at the Administrative Post Dom-Aleixo, Dili Municipality, 2025 - Guterres Magno, Mario Carlos; Moniz, Elias Pereira; Noviyanti, Noviyanti; Amaral Gaio, Frenania Ermelinda; Guterres Magno, Nuno Pedro (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Food poisoning resulting from biological contamination and inadequate food handling practices is a significant global public health concern. In Timor-Leste, the high number of restaurants that do not meet hygiene standards represents a real threat to food safety, particularly in food preparation. Objective: This study aimed to analyze the relationship between basic sanitation quality and the implementation of five key food safety practices and the quality of food preparation in restaurants in the Dom-Aleixo Administrative Region, Dili Municipality, in 2025. Method: This study used a quantitative analytical design with a cross-sectional approach. A total of 35 restaurants were sampled using an accidental sampling technique. Data were collected through questionnaires, observations, and interviews, and analyzed using the chi-square test. Results: 71.4% of restaurants had good basic sanitation quality and implemented food safety practices in accordance with WHO standards. There was a significant relationship between sanitation quality and food preparation quality (p < 0.001). All restaurants with poor sanitation also demonstrated food preparation that did not meet standards. Human factors, such as the knowledge and attitudes of food handlers, are key determinants of the implementation of food safety practices. Recommendation: Restaurant owners are advised to provide regular training to staff on sanitation and food safety. Local governments also need to strengthen monitoring systems and provide regular training. Further research is recommended, including direct observation, to obtain more detailed and objective data.